Nice to be on the A-List - Yasushi Hamao; Kenji Kutsuna; Joe Peek (Federal Reserve Bank of Boston, 2012)
This study uses Japanese data to address an important shortcoming of most of the existing literature on credit availability by including a set of unlisted firms (which are the firms most likely to be bank dependent) in the analysis, and by investigating differences between the treatment of listed and unlisted firms by their lenders. While we find evidence consistent with evergreening behavior by banks toward listed firms, whereby banks continue to lend to weak firms so they can continue making interest payments on existing loans and put off bankruptcy, the more striking result is that banks appear to be much less willing to engage in evergreening behavior toward the smaller, unlisted firms. Moreover, among listed firms, for which data on ownership by banks are available, a higher concentration of ownership of the firm by either the main bank or the firm's top three lenders increases the likelihood of the firm obtaining increased loans, suggesting that bank ownership of the firm stimulates evergreening behavior to a greater degree. However, the difference in treatment of unlisted firms relative to listed firms does not appear to be related simply to systematic differences in size between the two groups of firms. Thus, it appears that the distinguishing characteristic that determines whether a bank might evergreen loans to a firm is whether or not the firm is listed. Furthermore, this effect appears to be stronger for those firms listed on the more prestigious Tokyo Stock Exchange than for firms listed on other exchanges: being on the list (being listed) matters, and being on the A-list matters even more, consistent with a Too Connected To Fail phenomenon for nonfinancial firms in Japan.
Keywords: E44; E51; G21; G28; 330; SMEs; financial crisis; bank lending